2020
DOI: 10.1111/odi.13384
|View full text |Cite
|
Sign up to set email alerts
|

Overactivation of the NF‐κB pathway impairs molar enamel formation

Abstract: Objective Hypohidrotic ectodermal dysplasia (HED) is a hereditary disorder characterized by abnormal structures and functions of the ectoderm‐derived organs, including teeth. HED patients exhibit a variety of dental symptoms, such as hypodontia. Although disruption of the EDA/EDAR/EDARADD/NF‐κB pathway is known to be responsible for HED, it remains unclear whether this pathway is involved in the process of enamel formation. Experimental subjects and methods To address this question, we examined the mice overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Nrf2 absence in mice leads to an aberrant iron deposition in the papillary layer cells of the enamel organ and to altered ameloblasts, causing a loss of iron deposition on the enamel surface [ 38 ]. As the K5 promoter that we have used to direct the expression of ERAS is active in ameloblasts [ 39 , 40 , 41 ], it is conceivable that ERAS expression in this cell type may alter ameloblast functioning, resulting in a defective enamel iron deposition and discoloration.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 absence in mice leads to an aberrant iron deposition in the papillary layer cells of the enamel organ and to altered ameloblasts, causing a loss of iron deposition on the enamel surface [ 38 ]. As the K5 promoter that we have used to direct the expression of ERAS is active in ameloblasts [ 39 , 40 , 41 ], it is conceivable that ERAS expression in this cell type may alter ameloblast functioning, resulting in a defective enamel iron deposition and discoloration.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that both the IKKα and β subunits exhibit catalytic activity, while NEMO/IKKγ is involved in the recruitment of IκBs ( Barczewski et al, 2019 ). Moreover, IKKβ has been identified as the predominant kinase responsible for IκB phosphorylation ( Yamada et al, 2020 ; Jimi and Katagiri, 2022 ). The phosphorylation of IκBs triggers their polyubiquitination, proteasomal degradation by the 26s proteasome, and eventually the release of NF-κB transcription factor into the nucleus ( Chen and Greene, 2004 ).…”
Section: Genetic Basis Of the Eda/edar/nf-κb Signaling Pathwaymentioning
confidence: 99%
“…The phosphorylation of IκBs triggers their polyubiquitination, proteasomal degradation by the 26s proteasome, and eventually the release of NF-κB transcription factor into the nucleus ( Chen and Greene, 2004 ). NF-κB is a homo or heterodimer that can be formed from different combinations of RelA (p65), c-Rel, RelB, p50/p105 (NF-κB1), and p52/p100 (NF-κB2) ( Courtney et al, 2005 ; Yamada et al, 2020 ; Jimi and Katagiri, 2022 ). After the nuclear translocation of NF-κB, it induces the expression of genes essential for initiating and differentiating skin appendages such as hair, teeth, and sweat glands ( Figure 2 ).…”
Section: Genetic Basis Of the Eda/edar/nf-κb Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation